Monitoring adherence to vulvar lichen sclerosus treatment – a prospective study - Mallory L. Zaino; Jessica N. Pixley; Vani Mangalam Subramanian; Deepak Sirdeshmukh; Steven R. Feldman; Rita O. Pichardo (Journal of Dermatological Treatment)
Background: Vulvar lichen sclerosus treatment consists of topical corticosteroids followed by maintenance therapy. Self-reported adherence to topical corticosteroids in vulvar lichen sclerosus is approximately 66-70.4% and adherence to chronic topical medications is poor.Objective: To measure treatment adherence for vulvar lichen sclerosus.Methods: Adults with vulvar lichen sclerosus who were receiving or who were candidates to receive treatment with topical clobetasol propionate 0.05% ointment twice daily received medication tubes equipped with adherence monitors capturing the time and amount of dose dispensed. After 2 months, monitors were returned, and patients were surveyed regarding their adherence.Results: Ten patients participated for a median (range) of 8.5 (7–11) weeks. Eight (80%) and 7 (70%) caps captured medication timing and dosing events, respectively. Median (interquartile range) adherence was 65% (42–77) and median (interquartile range) medication dispensed per use was 0.15 (0.14 − 0.5) grams. Of the 8 patients using active adherence monitors, 2 did not clinically improve; adherence rates and mean quantity dispensed for these two patients were 31% and 0.13 grams, and 9% and 0.74 grams, respectively.Conclusion: Poor adherence to both twice daily application and prescribed medication quantity occurred frequently. Factors related to self-reported non-adherence included perceived greater efficacy, inconvenience, and time-constraints. Patient adherence to recommended treatment and clinical outcomes are areas for improvement in patients with vulvar lichen sclerosus.